Clinical Findings in Patients With Persistent Positional Nystagmus: The Designation of “Heavy and Light Cupula” - Tang, Xiaowu; Huang, Qiuhong; Chen, Ling; Liu, Peng; Feng, Tianci; Ou, Yongkang; Zheng, Yiqing (Frontiers in Neurology, 2019)
• Objective Direction-changing positional nystagmus (DCPN) had been observed as persistent horizontal apogeotropic years ago, which was considered as “cupulolithiasis or heavy cupula”. Recently, the concept of “light cupula” exhibiting persistent geotropic DCPN has been introduced. However, the light cupula is not clear systematic described, and the identification and diagnosis should be improved. Here we investigated the underlying characteristics and therapy, designed to the “light” and “heavy” cupula, summarized the clinical characteristics and therapeutic effect in the two groups. Methods A total of 359 cases with vertigo and bilateral DCPN were found in the supine roll test. Only 25 patients with persistent DCPN were enrolled and followed up. According to the direction of nystagmus, we divided the 25 patients into “heavy cupula” (apogeotropic) and “light cupula” (geotropic) groups. We compared the incidence, characteristics of nystagmus and the efficacy of repositioning maneuver in the two groups. Results There were 9 patients with persistent horizontal geotropic DCPN confirmed as “light cupula”, other 16 patients with persistent horizontal ageotropic DCPN were confirmed as heavy cupula. All of 25 patients had null plane, the mean value and standard deviation of the null plane in light cupula was 25.67±9.31°, and in heavy cupula was 27.06 ± 6.29°. The mean value and standard deviation of the termination plane in light cupula was 28.78±10.00°, and in heavy cupula was 30.25 ± 6.53°. There was no statistical significance between the two groups. We found that the direction of evoked nystagmus in the supine position in light cupula was toward the unaffected side, while in heavy cupula, toward to the affected side. The null plane appeared on the affected side.For light cupula patients, the effect was not obvious 7 days after the treatment, however, most of heavy cupula patients were effective. All patients basically recovered at 30 days. Conclusion The null plane is a very important and effective method to determine the affected side for light or heavy cupula. The short-term therapeutic effect of the light cupula is not good, while it is better in heavy cupula. However, the long-term prognosis both in light and heavy cupula are good.